A Camping Spree with Mr. Magee - Van Dusen, Chris (San Francisco : Chronicle Books, 2003)
Mr. Magee and his dog Dee go camping and have an adventure with a hungry bear.
Keywords: Camping -- Pictorial works; Juvenile fiction; Camping -- Juvenile fiction; Dogs -- Juvenile fiction; Bears -- Juvenile fiction; Stories in rhyme